PENGEMBANGAN STRATEGI INDUSTRI KREATIF MENGGUNAKAN VALUE CHAIN ANALYSIS - Wulan Suryandani; Novi Kusumaningsih (STIE Pelita Nusantara Semarang, 2021)
SMEs Batik Tulis Lasem as a regional product requires serious attention so that it has a competitive advantage, KUB Batik Tulis Lasem currently has a big enough role in product development and marketing for SMEs who are its members. However, program efforts and product development strategies, marketing techniques are still limited and government programs are still not on target. This condition causes Batik Tulis Lasem not having a high competitiveness. The aim of this research is to analyze the value chain of SMEs Batik Tulis Lasem using Value Chain Analysis. The method used is the Value Chain Analysis (VCA) approach combined with SWOT. The results of this study are for the priority of development strategies, it is obtained that KUB must do 1) innovate products, increase product variations 2) implement and optimize online marketing models 3) make attractive product packaging, 4) increase relationships with customers.